Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


(2x-3)(5x+2)= 2x(5x+2)-3(5x+2)= 10x^2+4x-15x-6=10x^2-11x-6

(3x-7)(4x-1)= 3x(4x-1)-7(4x-1)= 12x^2-3x-28x+7= 12x^2-31x+7

10x^2-11x-6+12x^2-31x+7= 10x^2+12x^2-11x-31x-6+7= 22x^2-42x+1

Therefore, (2x-3)(5x+2)+(3x-7)(4x-1)= 22x^2-42x+1
2 5 2
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts